2015
DOI: 10.1111/tmi.12579
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal dental periapical infections and pregnancy outcomes: results from a cross‐sectional study in Malawi

Abstract: Abstractobjectives Maternal infections are associated with intrauterine growth restriction (IUGR) and preterm birth (PTB). Dental infections are common in low-income settings, but their contribution to adverse pregnancy outcomes is unknown. We studied the epidemiology of dental periapical infections among pregnant women and their association to foetal growth restriction and the duration of pregnancy in a rural sub-Saharan African population.methods This was a cross-sectional study on the association between ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 28 publications
(30 reference statements)
0
51
2
1
Order By: Relevance
“…A recent study conducted in Malawi found a prevalence of 23.5% of periapical lesions in a sample of pregnant women. [20] Studies that were done in Western countries among the same age group, on the other hand, have found completely different results with excellent oral and dental health, which, as the researchers suggest, may reflect the use of fluoride and high levels of oral health education. [21] Taking into consideration the critical age range of our sample, the child bearing age, such patients may be susceptible to an increased risk of shorter pregnancy duration and intrauterine growth restriction as a result of such a high prevalence of periapical lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study conducted in Malawi found a prevalence of 23.5% of periapical lesions in a sample of pregnant women. [20] Studies that were done in Western countries among the same age group, on the other hand, have found completely different results with excellent oral and dental health, which, as the researchers suggest, may reflect the use of fluoride and high levels of oral health education. [21] Taking into consideration the critical age range of our sample, the child bearing age, such patients may be susceptible to an increased risk of shorter pregnancy duration and intrauterine growth restriction as a result of such a high prevalence of periapical lesions.…”
Section: Discussionmentioning
confidence: 99%
“…[21] Taking into consideration the critical age range of our sample, the child bearing age, such patients may be susceptible to an increased risk of shorter pregnancy duration and intrauterine growth restriction as a result of such a high prevalence of periapical lesions. [20]…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the predictor category included variables that described maternal characteristics in early pregnancy or the woman's direct exposures during the follow‐up (e.g., maternal nutrition or infection), whereas the intermediary variables were those that would follow from a primary exposure. The predictor and intermediate variables were selected either based on earlier literature (Brodsky & Christou, ) or because our own initial analyses had documented an association between them and newborn size (Harjunmaa et al, ; Stewart et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study results from Malawi indicated an association between maternal dental periapical infections (PAI) and shorter pregnancy duration and smaller birth size (Harjunmaa et al., ). PAI commonly develops when a deep caries lesion exposes the pulp of the tooth allowing oral bacteria to enter the dental root canals, from where the infection eventually spreads to the bone surrounding the root (Nair, ).…”
Section: Introductionmentioning
confidence: 99%
“…This study aimed to assess whether there is evidence of these two biologically plausible pathways between PAI and adverse pregnancy outcomes in a cohort of pregnant women from the iLiNS‐DYAD study in Malawi (Harjunmaa et al., ). Our main hypothesis was that the associations between PAI and shortened duration of pregnancy, lower birthweight, and smaller neonatal size are mediated through spread of the periapical bacteria to the feto‐placental unit (direct pathway) or systemic inflammation (indirect pathway).…”
Section: Introductionmentioning
confidence: 99%